P0084 Eribulin in patients with advanced urothelial cancer and previously treated with platinum and anti-microtubule chemotherapy: A phase 2 California Cancer Consortium trial. (July 2015) - Quinn, D.I.; Twardowski, P.W.; Ruel, N.; Groshen, S.G.; Dorff, T.B.; Pal, S.K.; Stadler, W.M.; Gandara, D.R.; Lara Jr, P.N.; Newman, E.M.
Abstract : Background: There is an unmet need for new agents in advanced urothelial cancer (UC). Antimicrotubule therapy (AMT; e.g. vincas and taxanes) has activity in UC. We previously reported that eribulin, a microtubule modulator derived from the black Pacific sea sponge, is highly active against metastatic UC in the clinical frontline setting and in patients who are treated with platinum but are naive to_AMT. Here, we report the results of a phase 2 study of patients with UC and previously treated with platinum and AMT. Methods: Eligible patients had UC of any histological type, calculated creatinine clearance of 20 mL/m 2 or more, and previously treated with platinum and AMT. Eribulin at 1.4 mg/m 2 was intravenously given on days 1 and 8, every 3 weeks. Overall response rate (RR) of more than 20% was considered promising for further study; 41 patients were required in a Simon two-stage design. Progression-free survival (PFS) and overall survival (OS) were secondary endpoints. Findings: Of 44 patients entered in this study, 37 were evaluated (seven too early). Patients included had a median age 68 years (range 25–86 years); 61% were men; Karnofsky performance score of 90% of more in 58% of patients; transitional cell histology 36 (86%); and Bajorin risk groups: 0: 23%, 1: 61%, 2: 16% (relative risk 25%, 95% confidence interval (CI) 12–38), including two complete responses and nine partial responses. Stable disease for more than 12 weeks was seen in 12 (27%) patients. At median 5.5 months of follow-up, median PFS was 3.9 months (2.8–5.1). Median OS was 8.4 months (5.3–14.0). PFS was associated with Bajorin risk group ( p  = 0.02 for trend). Toxicities included grade 3 or 4 neutropenia in 25 (57%) patients, febrile neutropenia (none reported), grade 3 anaemia in seven (16%) patients, and grade 1 or 2 sensory neuropathy in 17 (39%) patients. Interpretation: Eribulin has highly encouraging single agent activity in patients with advanced UC and previously treated with platinum and AMT. Phase 3 evaluation of eribulin in advanced UC is warranted. (NCT00365157; UM1 CA186717; U01 CA062505; P30 CA01408; P30 CA033572).